INTERFERENSI BAHASA MELAYU TERHADAP BAHASA INDONESIA (Analisis Fonologi, Morfologi, Sintaksis pada Pola Komunikasi Mahasiswa di UIN Sultan Syarif Kasim Riau) - Nugraheni, Aninditya Sri; Syuhda, Nisa (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2019)
This study aims to describe the process of interference ofMalay language on the Indonesian language;the analysis of phonology, morphology, and syntaxonthe students’ communication patterns at UIN Sultan Syarif Kasim, Riau. This is a field research study. The research was conducted on students majoring in Ibtidaiyah Madrasah Teacher Education at UIN Sultan Syarif Kasim by taking students’ communication patterns.Having takentheir communication pattern, the students are interviewed repeatedly to identify Malay language interference. In this case, there are several interferences found: Interference in the phonology and lexical field, which are divided into noun word class, verb word class, adjective word class, and pronoun word class.Interference in the grammatical field comprises interference in the field of morphology and syntax. Interference in the field of morphology includes affixation and repetition. The last, interference in the syntactic fieldinvolves the use of particles and phrase construction patterns.